2020
DOI: 10.3390/cancers12061419
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Metabolism in Development and Progression of Hepatocellular Carcinoma

Abstract: Metabolic reprogramming is critically involved in the development and progression of cancer. In particular, lipid metabolism has been investigated as a source of energy, micro-environmental adaptation, and cell signalling in neoplastic cells. However, the specific role of lipid metabolism dysregulation in hepatocellular carcinoma (HCC) has not been widely described yet. Alterations in fatty acid synthesis, β-oxidation, and cellular lipidic composition contribute to initiation and progression of HCC. The aim of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
91
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(92 citation statements)
references
References 186 publications
(235 reference statements)
0
91
1
Order By: Relevance
“…54 More recently, it has been reported that upregulation of AMPK activity, a typical nutrient deficiency condition, promoted the expressions of CPT-1 and CPT-2 and finally initiated the β-oxidation in HCC. 55 Hence, we observed the change of AMPK activation after LRP1B knockdown in HCC cells and found the upregulated activation of AMPK signaling. Herein, it…”
mentioning
confidence: 77%
“…54 More recently, it has been reported that upregulation of AMPK activity, a typical nutrient deficiency condition, promoted the expressions of CPT-1 and CPT-2 and finally initiated the β-oxidation in HCC. 55 Hence, we observed the change of AMPK activation after LRP1B knockdown in HCC cells and found the upregulated activation of AMPK signaling. Herein, it…”
mentioning
confidence: 77%
“…Although the Warburg effect and glutamine metabolism alterations are common processes in the metabolic reprogramming of tumors [ 21 , 22 ]. Mounting evidence also suggests that lipid metabolic reprogramming is essential for HCC development [ 23 ]. For instance, HCC cells typically exhibit enhanced de novo synthesis of fatty acids [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most important risk factors for HCC are HBV and HCV, the alcohol consumption and exposition to aflatoxin B1 [12,21]. The HBV or HCV related HCC are caused by chronical viral infection; whereas, the etiology of NBNC-HCC is mostly a metabolic dysregulation [27]. The tumor physiological features are quite different.…”
Section: Discussionmentioning
confidence: 99%